Theoretical interpretation of the concept of frame in Cognitive Linguistics - Alimova, Dilzoda Ikromjon qizi (The Lingua Spectrum, 2026)
This article examines the theoretical interpretation of the concept of frame in cognitive linguistics. The study aims to explore the origins, development, and major principles of Frame Semantics as proposed by Charles Fillmore and to explain the role of frames in the organization and interpretation of meaning. Particular attention is paid to the notions of semantic frames, frame elements, prototype effects, and FrameNet as a practical implementation of frame-semantic theory. The research employs descriptive, analytical, and comparative methods to investigate the theoretical foundations of the frame concept and its application in linguistic analysis. The findings demonstrate that frames function as cognitive structures that organize human knowledge and facilitate language comprehension by linking lexical meanings to broader conceptual contexts. The study concludes that Frame Semantics provides a comprehensive model for understanding the relationship between language, cognition, and cultural knowledge and remains one of the most influential approaches in contemporary cognitive linguistics.